Increased frequency of the autism broader phenotype in mothers transmitting etiological CNVs to sons affected by Autism Spectrum Disorder (ASD) - Asif, M. (2016)
Autism Spectrum Disorder (ASD) is a frequent and complex neurodevelopmental disorder, characterized by impairments in social communication and repetitive behaviors and with a high male to female ratio: ~4:1. Genetic factors, including rare Copy Number Variants (CNVs), have a substantial impact in ASD risk1, and are associated with specific phenotypic manifestations2. Recent studies reported that rare inherited CNVs are enriched in mothers of ASD children compared with mothers of controls and are preferentially transmitted from mothers to ASD children suggesting a sex bias in CNV transmission; further, the imbalanced transmission of small pathogenic CNVs from unaffected mothers to their sons with ASD has been described3,4. An increased prevalence of autism-like personality traits is found in unaffected relatives of ASD children, suggesting a genetic liability of a broader autism phenotype (BAP)5. The BAP in parents of autistic children can be assessed by the Social Responsiveness Scale (SRS)6 and Broad Autism Phenotype Questionnaire (BAPQ)7 reports. The SRS is 65-item questionnaire to identify sub-clinical social impairments and interpersonal behaviour in individuals. The BAPQ is a 36-item questionnaire measures social aloofness, rigid personality, and pragmatic language deficits in both parents and children.